Ageing: A Very Short Introduction - Pachana, Nancy A. (New York Oxford University Press, 2016)
Ageing entails lifelong dynamic changes in biological, psychological, and social functioning. While such changes in later adulthood were somewhat neglected by scientists in the past, recent decades have seen a marked increase in research in this area. Nancy A. Pachana examines the impact of rising numbers of older people worldwide.
Includes Index and Illustrations.
Keywords: Starzenie się